Health equity, social justice and human rights - McKay, Fiona H.; Taket, A. R. (Ann R.) (Routledge, 2020)
"This text demystifies systems set up for the protection and promotion of human rights globally, regionally and nationally. It explores the use and usefulness of rights-based approaches as an important part of the toolbox available to health and welfare professionals and community members working in a variety of settings to improve health and reduce health inequities"--